Efficacy of nebulized magnesium sulfate in moderate bronchiolitis - N Guruprasad; C A Gopalakrishna Mithra; Vinod H Ratageri (Wolters Kluwer Medknow Publications, 2022)
Background: Bronchiolitis is a common cause of illness and hospitalization in infants and young children. The effectiveness of various bronchodilators remains unclear. This study was conducted to assess the efficacy of nebulized magnesium sulfate in hospitalized children with moderate bronchiolitis in the age group of 1-24 months. Subjects and Methods: This was a prospective observational study done from December 2018 to June 2020. All children with moderate bronchiolitis (clinical severity score [CSS]-4-8) meeting inclusion/exclusion criteria were enrolled. A detailed history, demographic profile, CSS and oxygen saturation in room air, and heart rate were recorded. They were given two doses of magnesium sulfate in the form of nebulization for 10 min each, at 30 min apart. The children were assessed for CSS at 0 h, 1 h, and 4 h after nebulization. The children were considered improved if CSS <4 at the end of 4 h. The children were monitored for adverse reactions of magnesium sulfate. Results: Sixty children were enrolled. The mean age was 7.5 ± 6.47 months. Most children (51.7%) were in 1-6 months. The mean CSS scores at 0 h, 1 h, and 4 h were 6 ± 1.008, 2.95 ± 1.395, and 2.40 ± 1.564, respectively (P = < 0.001). Fifty-three (88.3%) children improved and seven (11.7%) children did not improve. In nonimproved group, subanalysis was done and found hypoxia (odds ratio − 12.6) as a significant risk factor. Flushing was the most common adverse effect noticed in eight (13.3%) children. Conclusions: Children with moderate bronchiolitis were improved with nebulized magnesium sulfate.